The sun does shine how I found life and freedom on death row - Hinton, Anthony Ray. (New York St. Martin's Press, 2018)
In 1985, Anthony Ray Hinton was arrested and charged with two counts of capital murder in Alabama. Stunned, confused, and only twenty-nine years old, Hinton knew that it was a case of mistaken identity and believed that the truth would prove his innocence and ultimately set him free.
Keywords: Hinton, Anthony Ray--Trials, litigation, etc